2023
DOI: 10.3390/foods12132448
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Spray-Drying Encapsulation of Sea Buckthorn Berry Oil

Abstract: The aim of this study was to evaluate the effect of spray-drying parameters on the physicochemical properties of encapsulated sea buckthorn berry oil. Different carriers (gum arabic, β-cyclodextrin, and their mixture (1:1, w/w)), inlet air temperatures (120, 150, and 180 °C), and carrier-to-oil ratios (2, 3, and 4, w/w) were evaluated. The obtained powders were characterized in terms of the product yield (36.79–64.60%), encapsulation efficiency (73.08–93.18%), moisture content (0.23–3.70%), hygroscopicity (1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…According to Da Veiga et al [20], increasing the temperature facilitates the drying process and reduces the surface tension and viscosity, which contributes to the formation of droplets leading to the greater efficacy of the spraydrying process. The same effect of drying temperature increase on the powder recovery was noticed by Alvarenga Botrel et al [14] who varied the drying temperature in the spray-drying of oregano EO in the range of 132-188 • C, and Čulina et al [45] who used 120, 150 and 180 • C as the drying temperature in the production of sea buckthorn berry oil powders.…”
Section: Powder Recoverysupporting
confidence: 57%
See 2 more Smart Citations
“…According to Da Veiga et al [20], increasing the temperature facilitates the drying process and reduces the surface tension and viscosity, which contributes to the formation of droplets leading to the greater efficacy of the spraydrying process. The same effect of drying temperature increase on the powder recovery was noticed by Alvarenga Botrel et al [14] who varied the drying temperature in the spray-drying of oregano EO in the range of 132-188 • C, and Čulina et al [45] who used 120, 150 and 180 • C as the drying temperature in the production of sea buckthorn berry oil powders.…”
Section: Powder Recoverysupporting
confidence: 57%
“…In comparison with other studies, the findings in this study are generally consistent with reported data, where Fernandes et al [11] and Felix et al [15] reported a solubility of 45.82% for rosemary EO powder and 37.38% for cinnamon EO powder, both containing MD:GA in a 1:1 ratio. Moreover, other authors [6,7,41,42,45] also confirmed decreased values for this reconstitution property when β-CD was included as the wall material. A mixture of MD and GA has already shown good solubility properties [46], for which the chemical constitution of the two wall materials is responsible.…”
Section: Solubilitymentioning
confidence: 64%
See 1 more Smart Citation
“…This characteristic could indicate the stability of particles regarding chemical and biological stresses during storage. The moisture content of SSEDS was of 1.5 ± 0.17% which was in the same order of magnitude as other dried particles obtained from spray drying process (Klinkesorn et al ., 2006; Čulina et al ., 2023). In our case, the moisture content was sufficiently low for dried powder in the food industry which exhibited moisture content between 3% and 4% (w/w) (Klaypradit & Huang, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal spray-drying process was obtained by superimposing the contour plots: an inlet air temperature of 162.5 • C and 25 g of maltodextrin per 100 g of beverage. Čulina et al [116] optimised the spray drying microencapsulation process of sea buckthorn pulp oil in their study. Increasing the inlet temperature during spray drying boosted product yield, encapsulation efficiency, and solubility, according to their studies.…”
Section: Spray Dryingmentioning
confidence: 99%